PHYLOGENETIC ASSESSMENT OF GIANT CLAMS (TRIDACNIDAE) USING PARTIAL AMINO ACIDS SEQUENCES OF CYTOCHROME C OXIDASE I GENE - Agus Nuryanto; Dedi Nuryadi; D. Soedharma; Blohm D (BIOTROPIA, 2007)
Phylogenetic assessment of the giant clams need to be improved using various genetic markers since their relaionships are plagued by inconsistency result of several studies. This is especially true for the species under sub-genus Chametrachea. Here we studied the phylogeny of the giant clams using amino acid sequence of the mitochondrial COI gene. This study is aimed to assess and better understand the relationships of the giant clams, especially for three species under subgenus Chametrachea. The result showed close proximity between T. crocea and T. squamosa and between T. maxima and T. gigas.Â  However, amino acids sequences of cytochrome c oxidase I gene was not strong enough to discriminate between T. crocea and T. squamosa. The majority of mutations were hydrophobic to hydrophilic amino acids.